From Compulsion to Volunteerism: Financing Kenduri Sko Events in the Framework of Sharia Economics as Kerinci's Indigenous Cultural Heritage - Nopita Sari; Ike Yulisa (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
Kenduri Sko is an open house tradition held in Lempur, where each household serves dishes to entertain guests from various regions. Despite the diverse economic conditions of the community, they collectively strive to provide dishes, even during financial limitations. This research aims to examine the transition of participation in Kenduri Sko events from being driven by obligation to a voluntary form of participation, which emerges from strong social and cultural values. The Islamic economic approach is used in this study to analyze the principles of justice, solidarity, and sharing reflected in the consumption and financing practices of Kenduri Sko events. The method used is a qualitative study with in-depth interviews and participatory observation of the Lempur community. The results show that despite facing economic challenges, the community remains committed to organizing kenduri as a form of respect for tradition and strengthening social relations. The research also highlights the social and economic implications of this practice as well as how this tradition contributes to the well-being of the community in Lempur. The contribution of this research is to provide an understanding of how Islamic economic values can be applied in the context of social traditions, as well as the important role of solidarity in strengthening social ties in an economically diverse society.